Fighting Bugs: Remove, Retry, Replicate, and Rejuvenate. - Grottke, Michael; Trivedi, Kishor S. (Computer (00189162), 2007)
The article discusses the types of bugs in computer software and the difficulty in detecting them. Bohrbugs are bugs that manifest themselves under well defined conditions. Also mentioned in the article are Mandelbugs and Age-Related bugs. Mandelbugs manifest themselves in system failures that are difficult to reproduce, whereas age-related bugs will manifest themselves is software that has not been rebooted for an extended period of time. The authors also offer some suggestions on how remove the bugs from the system. An example of an age-related bug that caused a system failure in the Gulf War is included.